Psychological consequenses of political repressions - Gailienė, Danutė (Genocidas ir rezistencija, 2025)
Extensive post–war psychological research over decades has shown that the trauma caused by war and political repression, both Soviet and Nazi, has long–lasting, even lifelong, psychological effects on some victims. These effects have little to do with personality predisposition: even for formerly healthy and well–adapted people, the shocking experiences have caused a range of mental health disorders, such as anxiety, nervousness, depression, recurrent nightmares, increased irritability and aggressiveness, a decline in their ability to work, etc.